2018
DOI: 10.1371/journal.pone.0201855
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced oxidative stress impairs proliferation and migration of human gingival fibroblasts

Abstract: Delayed gingival wound healing is widely observed in periodontal patients with diabetes. However, the molecular mechanisms of the impaired function of gingival fibroblasts in diabetes remain unclear. The purpose of this study was to investigate changes in the properties of human gingival fibroblasts (HGFs) under high-glucose conditions. Primary HGFs were isolated from healthy gingiva and cultured with 5.5, 25, 50, and 75 mM glucose for 72 h. In vitro wound healing, 5-ethynyl-2′-deoxyuridine (EdU), and water-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 46 publications
13
107
2
3
Order By: Relevance
“…Previous studies have reported that glucose induces ROS generation [14] and inhibits cell proliferation [21]. We first treated RPE with 15uM, 30uM, 50uM and 70uM glucose for 24h, 48h, 72h and 96h respectively, the cell counting and CCK-8 assay results showed that glucose inhibits RPE proliferation in a dose dependent manner (Figure 1A-D).…”
Section: Resultsmentioning
confidence: 74%
“…Previous studies have reported that glucose induces ROS generation [14] and inhibits cell proliferation [21]. We first treated RPE with 15uM, 30uM, 50uM and 70uM glucose for 24h, 48h, 72h and 96h respectively, the cell counting and CCK-8 assay results showed that glucose inhibits RPE proliferation in a dose dependent manner (Figure 1A-D).…”
Section: Resultsmentioning
confidence: 74%
“…Substantial evidence suggests that a high level of ROS impairs cell function and induces premature senescence in cells . The increased ROS production accelerates telomere shortening, induces the DNA damage response (DDR), and causes senescence growth arrest .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have documented that hyperosmolarity, as occurring in diabetic hyperglycemia, may represent important regulatory elements in uencing cell fate and viability, both in physiological and pathological conditions. These studies further report using glucose concentrations between 24mM -75 mM with incubation times up to 72 hr are su cient to mimic the diabetic oxidative stress response in different cellular types (human gingival broblasts and erythrocytes) [39,43]. Furthermore, exposure to a prolonged severe hyperglycemic (>30mM) load is correlated with increased susceptibility to cellular damage and severe inhibitory effects on nNOS/Nrf2.…”
Section: Discussionmentioning
confidence: 85%